Double Reed Instruments in Indonesia - Rithaony Hutajulu (Budapest International Research and Critics University, 2022)
In Indonesia various types of conical double reed instruments can be found across Sumatra mainly from the Northern part of Sumatra through Palembang in the South and on Java. This paper is a preliminary survey of conical double reed instruments in Indonesia. It aims to explore issues related to the origin and historical dissemination of these instruments in this region over different time periods and also the outside influences that have impacted the music cultures of this area. The paper will also discuss in general various types of reed instruments in the region, including their organological characteristics and the corresponding musical terminologies. This paper will also discuss in general various performance contexts and functions of the conical double reed instruments, including religious ceremonies, life/cycle rituals (weddings and funerals), and court ceremonial ensembles, among others.